2017
DOI: 10.1142/s0219477517500146
|View full text |Cite
|
Sign up to set email alerts
|

Trend Extraction in Functional Data of Amplitudes of R and T Waves in Exercise Electrocardiogram

Abstract: The R and T waves amplitudes of the electrocardiogram recorded during the exercise test undergo strong modifications in response to stress. We analyze the time series of these amplitudes in a group of normal subjects in the framework of functional data, performing reduction of dimensionality, smoothing and principal component analysis. These methods show that the R and T amplitudes have opposite responses to stress, consisting respectively in a bump and a dip at the early recovery stage. We test these features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Finally, in our study we also observed greater T‐wave amplitude at the finish‐line evaluation as compared with ECG data collected the day before the competition, in absence of relevant differences between men and women . During exercise T‐wave magnitude tends to lessen, showing a marked increase in the first minutes of recovery . R‐ and T‐wave amplitudes have opposite responses to stress, consisting, respectively, in a bump and a dip at the early recovery stage .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, in our study we also observed greater T‐wave amplitude at the finish‐line evaluation as compared with ECG data collected the day before the competition, in absence of relevant differences between men and women . During exercise T‐wave magnitude tends to lessen, showing a marked increase in the first minutes of recovery . R‐ and T‐wave amplitudes have opposite responses to stress, consisting, respectively, in a bump and a dip at the early recovery stage .…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that profiles of R‐ and T waves could reflect hemodynamic variables that occur in healthy subjects during exercise. According to the Frank‐Starling law, opposite trends in R‐ and T‐ wave amplitude seem to reflect tele‐diastolic and tele‐systolic volume changes, respectively, and increasing tele‐diastolic volume leads to an increase in electrical resistivity due to higher number of red cells in LV while reducing tele‐systolic volumes are associated with an increase in T‐wave amplitude. Accordingly, the demonstration of a greater T‐wave amplitude after the race, as compared with pre‐race data, might be the physiological consequence of the increased inotropic response acutely induced by the race and should be interpreted as a physiological phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Random time series are often recorded when a slowly changing component (trend) disturbs their further analysis, especially at low frequency ranges. This e®ect is observed in various experiments and data [1][2][3]. Therefore, new and e±cient methods are required to analyze random data generated in recently developed new electronic devices and structures.…”
Section: Introductionmentioning
confidence: 99%